The theoretical and practical problems of applying military occupation in international law (Journal of Human Sciences, 2023)
It’s generally accepted that law in general, and international law in particular, is a reflection of the developments that occur in societies and civilizations, so they change and adapt to match the needs of individuals, and an aspect of international jurisprudence also pushes the need to abandon the classic boundaries drawn by members of the international community in the relations that unite them. The need to respond to the humanitarian necessities resulting from disasters resulting from the outbreak of various armed conflicts, whether international or non-international, was the emergence of what is termed humanitarian intervention through which some countries aim to protect the rights of victims of armed conflicts through military intervention in the battlefield, It is the same logic to which a number of jurists are subject, who believe that the occupying state can transgress its obligations towards the occupying state when military necessity requires it, or when it is a radical response to protect human rights in the occupied state. This paper deals with the issue of the prevailing ideological dispute over the issue of the legitimacy of belligerent occupation, and the parameters that delineate its limits in light of the scarcity of legal texts that address this issue, and thus presents the echo of the transcendent voices calling for the need to develop this concept in a pragmatic manner that responds to the basic righ of individuals.